2009
DOI: 10.1002/anie.200900189
|View full text |Cite
|
Sign up to set email alerts
|

The Regio‐ and Stereoselective Synthesis of trans‐2,3‐Dihydropyridine N‐oxides and Piperidines

Abstract: Reactivity N-Own: Pyridine N-oxides can be used for the complete regio- and stereoselective synthesis of trans-substituted piperidines. The sequential addition of Grignard reagents and aldehydes or ketones to pyridine N-oxides yields a complete regio- and stereoselective trans 2,3-addition reaction in high yields, and the substituted 2,3-dihydropyridine N-oxide can be reduced to form 2,3-trans-substituted piperidines (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In the context of the present work, it is interesting to compare the corresponding steps in the reduction of pyridine N-oxide to piperidine N-oxide (Equation (9)). In contrast to Equations (7) and (8), there were no corresponding experimental data for Equation (9) [ 50 ]. Indeed, catalytic hydrogenation of pyridine N-oxide produced pyridine [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the present work, it is interesting to compare the corresponding steps in the reduction of pyridine N-oxide to piperidine N-oxide (Equation (9)). In contrast to Equations (7) and (8), there were no corresponding experimental data for Equation (9) [ 50 ]. Indeed, catalytic hydrogenation of pyridine N-oxide produced pyridine [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on comparison of ΔH1 (pyridine N-oxide) and ΔH3 (benzene), the overall calculated resonance energy in pyridine N-oxide was 28.7 kcal/mol (B3LYP/6-31G*) or 34.2 (8) In the context of the present work, it is interesting to compare the corresponding steps in the reduction of pyridine N-oxide to piperidine N-oxide (Equation ( 9)). In contrast to Equations ( 7) and ( 8), there were no corresponding experimental data for Equation ( 9) [50]. Indeed, catalytic hydrogenation of pyridine N-oxide produced pyridine [51].…”
Section: Resonance Energy In Pyridine N-oxidementioning
confidence: 95%
“…This finding was further confirmed by 2D-NMR, noesy and hmbc experiments, and the elucidation of a crystal structure. 23 Furthermore, H-NMR analysis of the crude reaction mixture confirmed that the 2,3-trans dihydropyridine N-oxide 17a isomer was formed exclusively, with the cis isomer not being detected at all. The diastereomeric mixture formed in the reaction results from the third stereocentre created at the benzylic carbon.…”
Section: Methodsmentioning
confidence: 92%
“…diastereomeric ratio (dr) of 82/18, is rather impressive, especially considering that three stereocentra are formed in one reaction step (Scheme 9). 23 Further investigation of the scope of the reaction was performed with different pyridine N-oxides 1 and PhMgCl followed by sequential addition of benzaldehyde, butyraldehyde or cyclohexanone. These experiments demonstrated that the reaction is compatible with these electrophiles (Scheme 10).…”
Section: Synthesis Of Substituted Piperidinesmentioning
confidence: 99%
“…Almquist and coworkers have shown that organo-magnesium reagents can add to pyridinium N-oxides selectively at the C-2 position in the presence of suitable electrophiles (e.g., benzaldehyde) to obtain functionalized trans-2,3-dihydropyridines (1.52) in a completely regio-and stereoselective process (Scheme 1.13). 56 Another potentially powerful tool for heterocyclic synthesis is asymmetric addition of nucleophiles to activated pyridine substrates. Even though this has proven to be effective with the use of stoichimetric chiral auxiliaries, there are only a few reports describing catalytic asymmetric additions of nucleophiles to pyridinium salts.…”
Section: Dearomatization Of Pyridine Substratesmentioning
confidence: 99%